EFEK PEMANGKASAN AKAR DAN PEMANGKASAN PELEPAH TERHADAP KUALITAS HASIL MINYAK KELAPA SAWIT (ELAEIS GUINEENSIS JACQ) PADA UMUR YANG BERBEDA - M. Amrul Khoiri; Jajang Sauman Hamdani; Cucu Suherman; Ruminta Ruminta (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2020)
Efforts to intensify oil palm (Elaeis guineensis Jacq.) are needed to increase productivity close to the actual production potential of oil palm crops. The productivity and growth of oil palm is partly controlled by the relationship between the top of the plant (the leaf) and the bottom of the plant (root). This study aims to find out the effect of root pruning and the number of fronds on the growth, production and quality of oil palm products. The research was conducted for 12 months from February 2018 to January 2019 in gardens owned by the community of Petapahan Village, Tapung District of Kampar Regency, Riau. The research was conducted experimentally using split plot design which is grouped based on different plant age (5 years, 10 years and 15 years). The main plot is the pruning of oil palm, Normal, Light, and Heavy fronds. The plot is trimming the roots of oil palm 75%, 50% and 25%. The results showed that root pruning and the number of fronds did not affect the interaction of observational premeters. Pruning the roots independently gives a noticeable influence on the content of mesocarp oil. Self-trimming of the fronds has a real effect on the total increase in oil. Plant life has a noticeable effect on enhancement, total oil, mesocarp oil and free fatty acids.